2007
DOI: 10.1108/02683940710726447
|View full text |Cite
|
Sign up to set email alerts
|

When person‐organization (mis)fit and (dis)satisfaction lead to turnover

Abstract: PurposeThe present study examined the relationships between P‐O fit, job satisfaction, perceived job mobility, and intent to turnover. It was hypothesized that job satisfaction mediated the P‐O fit‐intent to turnover relationship and that perceived job mobility moderated the job satisfaction‐intent to turnover relationship such that the combined effect of high job dissatisfaction and high perceived job mobility predicted intent to turnover.Design/methodology/approachData were obtained utilizing a field survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
184
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(224 citation statements)
references
References 43 publications
(98 reference statements)
19
184
0
6
Order By: Relevance
“…Feng (2011) concluded that person-organization fit (POF) is positively related to organization's innovative climate. Results match previous studies, such as Kristof-Brown et al (2005), Scott and Bruce (1994), Verquer et al (2003), Wheeler et al (2007), etc. Also, psychological climate adjustment is positivity related to organization's innovative climate as shown by Burke and Litwin (1992), Carless (2004), James and Jones (1974), Parker et al (2003), Tierney (1999).…”
Section: The Conceptual Framework and Hypothesissupporting
confidence: 81%
See 1 more Smart Citation
“…Feng (2011) concluded that person-organization fit (POF) is positively related to organization's innovative climate. Results match previous studies, such as Kristof-Brown et al (2005), Scott and Bruce (1994), Verquer et al (2003), Wheeler et al (2007), etc. Also, psychological climate adjustment is positivity related to organization's innovative climate as shown by Burke and Litwin (1992), Carless (2004), James and Jones (1974), Parker et al (2003), Tierney (1999).…”
Section: The Conceptual Framework and Hypothesissupporting
confidence: 81%
“…ASA (attraction-selection attrition) theory suggests that people are interested in specific companies and jobs that suit their interest and personalities (Schneider, 1987) which draw the relationship between job criteria and decision-making process for selection towards company attractiveness (Dineen et al, 2002;Ehrhart and Ziegert, 2005). Previous studies found out that innovative climate is not easy to maintain (Kristof-Brown et al, 2005;Scott and Bruce, 1994;Verquer et al, 2003;Wheeler et al, 2007). Holland (1976) proved that there is a similarity between career environments and the people that join them.…”
Section: Person-organization Fit (Pof) and Innovative Climatementioning
confidence: 99%
“…Subsequently, person-organization fit has been found to be an important facet within the organization-individual relationship because higher levels of fit resulted in positive organizational outcomes. Previous studies have found person-organization fit to increase positive outcomes such as job satisfaction, organizational commitment, organizational citizenship behavior, and performance while decreasing detrimental outcomes such as employee deviance (e.g., [36][37][38]). …”
Section: Person-csr Fitmentioning
confidence: 99%
“…First, although both forms of fit have long been the centre of attention for organizational behaviour and industrial/organizational psychology, studies have largely focused on examining them separately (e.g., Guan, Deng, Bond, Chen, & Chan, 2010;Mostafa & Gould-Williams, 2014;Singhal & ChatterJee, 2006;Wheeler, Gallagher, Brouer, & Sablynski, 2007) rather than incorporating both types in a single model. Second, most of the available research examined the roles of the P-J fit and P-O fit in respect of various individual and organizational outcomes, such as job satisfaction (Biswas & Bhatnagar, 2013;Wheeler et al, 2007), organizational commitment (Biswas & Bhatnagar, 2013), organizational citizenship behaviour (Cable & DeRue, 2002) and turnover (Arthur et al, 2006). In doing so, most often studies investigated that how antecedents predict outcomes.…”
Section: Introductionmentioning
confidence: 99%